Pengaruh Corporate Social Responsibility (CSR) terhadap Kinerja Keuangan Perusahaan pada Sub Sektor Industri Farmasi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Amanda, Kiki; Ermaini, Ermaini; Wiarta, Iqra; Dani, Rian; Dewi, Lizabeth Sari (J-MAS (Jurnal Manajemen dan Sains), 2024)
This study is entitled The Effect of Corporate Social Responsibillity (CSR) on the Company's Financial Performance in the Pharmaceutical Sub-Sector for the 2019-2023 Period. The purpose of this study is first to determine the effect of Corporate Social Responsibillity (CSR) on Return On Assets (ROA). Second, to determine the effect of Corporate Social Responsibillity (CSR) on Return On Equity (ROE). Third, to determine the effect of Corporate Social Responsibillity (CSR) on Gross Profit Margin (GPM). Fourth, to determine the effect of Corporate Social Responsibillity (CSR) on Nett Profit Margin (NPM). The research method used is quantitative, this type of research data is secondary data using a simple regression equation model. The results showed that CSR has no effect on ROA with a significant value of 0.193 greater than 0.05, CSR has no effect on ROE with a significant value of 0.568 greater than 0.05, CSR has no effect on GPM with a significance value of 0.059 greater than 0.05, and CSR has no effect on NPM with a significance value of 0.451 greater than 0.05, which means that companies that are active in CSR activities do not always tend to have better financial performance. CSR is one of the company's strategies to improve its image and reputation, which is expected to contribute to improved financial performance.